Fabrication of porous MgAl2O4 ceramics using V2O5 as sintering additive. Issue 14 (1st October 2020) - Han, Lei; Li, Faliang; Yao, Xingyu; Dong, Longhao; Luo, Mengting; Zhang, Haijun; Jia, Quanli; Zhang, Shaowei
Abstract: MgAl2 O4 ceramics with high porosity and performance were fabricated via foam gel casting at 1673–1823 K using MgAl2 O4 as the raw material and a small amount of V2 O5 (0.25 wt%) as a sintering additive. The variations in the physical properties of the final porous MgAl2 O4 samples at ambient temperature demonstrated that their flexural, compressive, and specific strength increased with the addition of a small amount of V2 O5 as a sintering aid. However, the thermal insulation properties of the as-fabricated MgAl2 O4 ceramics exhibited an inverse tendency. A porous MgAl2 O4 ceramic containing 0.25 wt% of V2 O5 and fired at 1823 K had flexural and specific strength values of 4.2 MPa and 14.0 (MPa cm 3 )/g, respectively, representing improvements over those reported in the literature at a similar porosity (72.0%). Moreover, a low thermal conductivity of approximately 0.24 W/(m·K) was measured at 473 K, which may be attributed to the relatively high porosity and high proportion of small pores with diameters less than 50 μm.